The spider mite saga: quest for biorational management strategies - Ibrahim, Yusof (Bahagian Komunikasi Korporat, Universiti Putra Malaysia, 2004)
The losses that growers have to absorb due to spider mites can be very discouraging. In spite of the use of acaricides which has understandably been short-term, the loss incurred in the Cameron Highlands ranged between 10-50% annually. The spider mite is quick in overcoming practically all chemicals currently available in the market, thus new compounds have to be used incessantly. Such situations will enhance the potential for the development of genetic resistance. As complete elimination of the spider mite is almost impossible, biological agents can play a significant role in the reduction of mite population, even though they may not function as reliably as chemical pesticides in every situations. Information on the bioecological demographic performance of two indigenous predatory mite species has indicated that they are potentially effective suppressors of spider mite population. A programme of intermittent inundative release sufficiently enhanced by selective acaricide could form the basis for an integrated mite management (IMM) system. Additional microbial control agents in the form of sprayable entomopathogenic fungi indigenous to Malaysia are now available to complement the action of the predators, and can perhaps serve as a plausible alternative to unilateral reliance on chemical acaricides. Hence, an integrated management system to control spider mites can be put in place so that food crops free from pesticide residue can be made available to the consumers.